2010
DOI: 10.1186/1743-422x-7-207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of CD127 expression on memory CD8 T cells from patients with chronic hepatitis B during telbivudine treatment

Abstract: BackgroundAccumulating evidence supports the theory that expression of CD127 on CD8 T cells during the process of antiviral immune response indicates a subset of effect CD8 T cells that successfully develop into fully protective memory. CD8 T cells expression of CD127 may be used as a predictor to evaluate disease status in chronic viral infection. The aim of this study was to investigate the CD127 expression level on different subsets of CD8 T cell and explore the relationship between CD127 expression on CD8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…19,20 Coincidently, clinical investigations reported that exhausted CD8 1 T cells downregulated their cell surface expression of the a chain of the IL-7 receptor (IL-7R; CD127) in chronic hepatitis B virus and hepatitis C virus patients. 14,21,22 Consistent with these observations, Pellegrini and colleagues 23 demonstrated that IL-7 treatment decreased PD-1 expression and reversed T-cell exhaustion in chronic LCMV infection. These reports imply that IL-7/IL-7R signaling in CD8 1 T cells may also affect their functions and fate in acute viral hepatitis.…”
Section: Introductionsupporting
confidence: 64%
“…19,20 Coincidently, clinical investigations reported that exhausted CD8 1 T cells downregulated their cell surface expression of the a chain of the IL-7 receptor (IL-7R; CD127) in chronic hepatitis B virus and hepatitis C virus patients. 14,21,22 Consistent with these observations, Pellegrini and colleagues 23 demonstrated that IL-7 treatment decreased PD-1 expression and reversed T-cell exhaustion in chronic LCMV infection. These reports imply that IL-7/IL-7R signaling in CD8 1 T cells may also affect their functions and fate in acute viral hepatitis.…”
Section: Introductionsupporting
confidence: 64%
“…The presence of CD127 on CD8+ T cells during the antiviral immune responses is thought to be a biomarker of effector T cells that successfully mature into highly proliferative protective memory T cells [33], [34]. Thus, loss of CD127 expression would be detrimental to long-term memory T cell maintenance and immune surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that after 52 weeks of telbivudine treatment, the HBeAg loss rate is approximately 26% higher than that for other nucleoside analogues . Some research suggests that telbivudine has immunoregulatory effects . Thus, patients with partial responses to pegylated interferon who switch to telbivudine may achieve a high seroconversion rate, as shown in a study from China .…”
Section: Discussionmentioning
confidence: 96%